Adaptive management assists reintroduction as higher tides threaten an endangered salt marsh plant. Issue 4 (25th March 2019) - Noe, Gregory B.; Fellows, Meghan Q.N.; Parsons, Lorraine; West, Janelle; Callaway, John; Trnka, Sally; Wegener, Mark; Zedler, Joy
Abstract : In theory, extirpated plant species can be reintroduced and managed to restore sustainable populations. However, few reintroduced plants are known to persist for more than a few years. Our adaptive‐management case study illustrates how we restored the endangered hemiparasitic annual plant, Chloropyron maritimum subsp. maritimum (salt marsh bird's beak), to Sweetwater Marsh, San Diego Bay National Wildlife Refuge, California, United States, and used monitoring and experimentation to identify the factors limiting the reintroduced population. After extirpation in 1988, reintroduction starting that year led to a resilient, genetically diverse population in 2016 (a "boom" of approximately 14, 000) that rebounded from a "bust" (62 in 2014). Multiple regressions attributed 82% of the variation in population counts to tidal amplitude, rainfall, and temperature. Populations of salt marsh bird's beak crashed when the diurnal tide range peaked during the 18.6‐year lunar nodal cycle (a rarely considered factor that periodically added approximately 12 cm to tidal ranges). We explain booms as follows: During smaller tidal amplitudes, above‐average rainfall could desalinize upper intertidal soils and stimulate salt marsh bird's beak germination. Then, moderate temperature in May favors growth to reproduction in June. In addition, salt marsh bird's beak needs a short and open canopy of native perennial plants, with roots to parasitize (not non‐native annual grass pseudohosts) and nearby upland soil for a preferred pollinator, ground‐burrowing bees. Although our reintroduced salt marsh bird's beak population is an exceptional case of persistence, this rare species‐specific environmental and biological requirement makes it vulnerable to rising sea levels and global warming.